Periodic Route Optimization for Handed-off Connections in Wireless ATM Networks - Salah, Khaled (1999)
In Wireless ATM networks, user connections need to be rerouted during handoff as mobile users move among base stations. The rerouting of connections must be done quickly with minimal disruption to traffic. In addition, the resulting routes must be optimal. A reasonable approach is to implement handoff in two phases. In the first phase connections are rapidly rerouted and in the second phase a periodic route optimization procedure is executed. The route optimization should impose minimal signaling and processing load on the ATM switches. In this paper, we propose and study a periodic execution of route optimization for a two-phase handoff scheme. We study two types of execution: non-adaptive and adaptive. For the adaptive optimization, we consider two adaptation schemes that are dependent on network conditions. A simulation model is developed to study system performance. The adaptive route optimization is shown to minimize signaling and processing load while maximizing utilization of reserved resources.